Penerapan Model Pembelajaran Discovery Learning Melalui Pembelajaran Berdiferensiasi untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Matematika di Kelas IV SD Negeri 27/IX Sebapo - Haryanti, Meli; Sastrawati, Eka; Rosmalinda, Desy (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to describe how the application of the discovery learning model through differentiated learning to improve student learning outcomes in mathematics subjects of data building material in class IV Elementary School. This research is a class action research (PTK) consisting of two cycles, where the data taken in the form of observation data through teacher observation sheets in applying the discovery learning model through differentiated learning and observation sheets of student learning outcomes in the form of post tests. This research was conducted with 4 stages, namely, planning, implementation, observation, and reflection. The research was conducted at SDN 27/IX Sebapo from January to February 2024. The results of this study indicate an increase in student math learning outcomes as seen from the student learning outcomes test sheet in the pre-action student learning outcomes of 35%. Experienced an increase in cycle I meeting 1 to 39%, then experienced an increase again in cycle II meeting 2 to 58%, and increased again in cycle II meeting 1 which was 69%, then increased again in cycle II meeting 2 to 88% with category A (very good). Based on the findings of the research results, it can be concluded that student learning outcomes on flat building material in class IVb SDN 27/IX Sebapo can increase after applying the discovery learning model through differentiated learning.